[latexpage]The Lagrangian is another mathematical tool of Kuhn and Tucker for solving linear and nonlinear constrained maximization program. Instead of maximizing $U$, it maximizes $\Lambda$. Considering the program,
$\left\{ \begin{array}{c} \max_{k_{t+1},h_{t}}\sum\nolimits_{0}^{\infty }\beta ^{t}\left( \ln c_{t}+A\ln \left( 1-h_{t}\right) \right) \\ sc:f\left( \lambda _{t},k_{t},h_{t}\right) =\lambda _{t}\left( k_{t}\right) ^{\theta }\left( h_{t}\right) ^{1-\theta } \\ sc:k_{t+1}=\left( 1-\delta \right) k_{t}+i_{t} \\ sc:f\left( \lambda _{t},k_{t},h_{t}\right) \geq c_{t}+i_{t} \end{array} \right.$ We write the Lagrangian as the sum of the objective function and the constraints weighted by a Lagrange multiplier associated with each of these constraints. As the optimization is also an infinity of time, the Lagrangian is dynamic. The constraint (1) and (3) can be reduced by one to simplify the calculations. We must therefore adapt our maximization program by summing the constraints with two Lagrange multipliers $\zeta _{t}$ et $\upsilon _{t}$,
$\Lambda \left( \zeta _{t},\upsilon _{t}\right) =\max_{k_{t+1},h_{t}}\sum\nolimits_{0}^{\infty }\beta ^{t}\left( \begin{array}{c} \left( \ln c_{t}+A\ln \left( 1-h_{t}\right) \right) \\ -\zeta _{t}\left[ \lambda _{t}\left( k_{t}\right) ^{\theta }\left( h_{t}\right) ^{1-\theta }-\left( c_{t}+i_{t}\right) \right] \\ -\upsilon _{t}\left[ \left( 1-\delta \right) k_{t}+i_{t}-k_{t+1}\right] \end{array}% \right)$ We must now determine the gradients (or extremas), according to the Lagrangian variables to maximize,
\begin{eqnarray*}
\quicklatex{size=16}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{%
\partial k_{t+1}}=0 \\
&\Leftrightarrow &-\beta ^{t}\upsilon _{t}-\beta ^{t+1}\left( \zeta
_{t+1}\theta \lambda _{t+1}\left( \frac{k_{t+1}}{h_{t+1}}\right) ^{\theta
-1}+\upsilon _{t+1}\left( 1-\delta \right) \right) =0 \\
&\Leftrightarrow &-\zeta _{t+1}r_{t}+\upsilon _{t+1}\left( 1-\delta \right) =%
\frac{\upsilon _{t}}{\beta }
\end{eqnarray*}
\begin{eqnarray*}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{%
\partial h_{t}}=0 \\
&\Leftrightarrow &\beta ^{t}\left( A\frac{-1}{1-h_{t}}-\zeta _{t}\left(
1-\theta \right) \lambda _{t}\left( k_{t}\right) ^{\theta }\left(
h_{t}\right) ^{-\theta }\right) =0 \\
&\Leftrightarrow &A\frac{-1}{1-h_{t}}=\zeta _{t}\left( 1-\theta \right)
\lambda _{t}\left( \frac{k_{t}}{h_{t}}\right) ^{\theta } \\
&\Leftrightarrow &A\frac{-1}{1-h_{t}}=\zeta _{t}w_{t}
\end{eqnarray*}
The Lagrangian has two additional variables to be determined, it is also much more gradients than there are constraints,
\begin{eqnarray*}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{
\partial c_{t}}=0 \\
&\Leftrightarrow &\beta ^{t}\left( \frac{1}{c_{t}}+\zeta _{t}\right) =0 \\
&\Leftrightarrow &\frac{1}{c_{t}}=-\zeta _{t}
\end{eqnarray*}
\begin{eqnarray*}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{
\partial i_{t}}=0 \\
&\Leftrightarrow &\beta ^{t}\left( -\zeta _{t}-\upsilon _{t}\right) =0 \\
&\Leftrightarrow &-\zeta _{t}=\upsilon _{t}=\frac{1}{c_{t}}
\end{eqnarray*}
Our four first-order conditions, after a little algebra, lead us to find,
$\left\{ \begin{array}{c} \frac{c_{t+1}}{\beta c_{t}}r_{t}+\left( 1-\delta \right) \\ Ac_{t}=\left( 1-h_{t}\right) w_{t}% \end{array}% \right.$ If the Lagrangian is slightly longer from a pure mathematical point of view, it has the advantage of simplifying the optimization problem. From experience, calculation errors are much less frequent using the Lagrangian with respect to partial derivatives.[latexpage]Le Lagrangien est un autre outil mathématique de Kuhn et Tucker pour la résolution de programme de maximisation sous contrainte linéaire et non linéaire. Au lieu de maximiser $U$, on maximise $\Lambda$. En considérant le programme,
$\left\{ \begin{array}{c} \max_{k_{t+1},h_{t}}\sum\nolimits_{0}^{\infty }\beta ^{t}\left( \ln c_{t}+A\ln \left( 1-h_{t}\right) \right) \\ sc:f\left( \lambda _{t},k_{t},h_{t}\right) =\lambda _{t}\left( k_{t}\right) ^{\theta }\left( h_{t}\right) ^{1-\theta } \\ sc:k_{t+1}=\left( 1-\delta \right) k_{t}+i_{t} \\ sc:f\left( \lambda _{t},k_{t},h_{t}\right) \geq c_{t}+i_{t} \end{array} \right.$ On écrit le lagrangien comme la somme de la fonction objectif avec ses contraintes pondérées par un multiplicateur de Lagrange associé à chacune de ces contraintes. Comme l’optimisation porte également sur une infinité de périodes, le lagrangien est donc dynamique. Les contraintes (1) et (3) peuvent être réduites en une pour simplifier les calculs. Il faut donc reprendre notre programme de maximisation en sommant chaque contrainte pondérée par deux multiplicateurs de Lagrange $\zeta _{t}$ et $\upsilon _{t}$,
$\Lambda \left( \zeta _{t},\upsilon _{t}\right) =\max_{k_{t+1},h_{t}}\sum\nolimits_{0}^{\infty }\beta ^{t}\left( \begin{array}{c} \left( \ln c_{t}+A\ln \left( 1-h_{t}\right) \right) \\ -\zeta _{t}\left[ \lambda _{t}\left( k_{t}\right) ^{\theta }\left( h_{t}\right) ^{1-\theta }-\left( c_{t}+i_{t}\right) \right] \\ -\upsilon _{t}\left[ \left( 1-\delta \right) k_{t}+i_{t}-k_{t+1}\right] \end{array}% \right)$ Il faut désormais déterminer les gradients, ou extremums, du Lagrangien en fonction des variables à maximiser,
\begin{eqnarray*}
\quicklatex{size=16}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{%
\partial k_{t+1}}=0 \\
&\Leftrightarrow &-\beta ^{t}\upsilon _{t}-\beta ^{t+1}\left( \zeta
_{t+1}\theta \lambda _{t+1}\left( \frac{k_{t+1}}{h_{t+1}}\right) ^{\theta
-1}+\upsilon _{t+1}\left( 1-\delta \right) \right) =0 \\
&\Leftrightarrow &-\zeta _{t+1}r_{t}+\upsilon _{t+1}\left( 1-\delta \right) =%
\frac{\upsilon _{t}}{\beta }
\end{eqnarray*}
\begin{eqnarray*}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{%
\partial h_{t}}=0 \\
&\Leftrightarrow &\beta ^{t}\left( A\frac{-1}{1-h_{t}}-\zeta _{t}\left(
1-\theta \right) \lambda _{t}\left( k_{t}\right) ^{\theta }\left(
h_{t}\right) ^{-\theta }\right) =0 \\
&\Leftrightarrow &A\frac{-1}{1-h_{t}}=\zeta _{t}\left( 1-\theta \right)
\lambda _{t}\left( \frac{k_{t}}{h_{t}}\right) ^{\theta } \\
&\Leftrightarrow &A\frac{-1}{1-h_{t}}=\zeta _{t}w_{t}
\end{eqnarray*}
Le Lagrangien dispose de deux variables supplémentaires à déterminer, il faut par ailleurs autant de gradients supplémentaires qu’il n’y a de contraintes,
\begin{eqnarray*}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{
\partial c_{t}}=0 \\
&\Leftrightarrow &\beta ^{t}\left( \frac{1}{c_{t}}+\zeta _{t}\right) =0 \\
&\Leftrightarrow &\frac{1}{c_{t}}=-\zeta _{t}
\end{eqnarray*}
\begin{eqnarray*}
FOC &:&\frac{\partial \Lambda \left( \zeta _{t},\upsilon _{t}\right) }{
\partial i_{t}}=0 \\
&\Leftrightarrow &\beta ^{t}\left( -\zeta _{t}-\upsilon _{t}\right) =0 \\
&\Leftrightarrow &-\zeta _{t}=\upsilon _{t}=\frac{1}{c_{t}}
\end{eqnarray*}
Nos quatre conditions du premier ordre, après un peu d’algèbre, nous amènent à retrouver,
$\left\{ \begin{array}{c} \frac{c_{t+1}}{\beta c_{t}}r_{t}+\left( 1-\delta \right) \\ Ac_{t}=\left( 1-h_{t}\right) w_{t}% \end{array}% \right.$ Si le Lagrangien est légèrement plus long du point de vue algébrique, il a l’avantage de simplifier le problème d’optimisation. Par expérience, les erreurs de calcul sont beaucoup moins fréquentes via le lagrangien par rapport aux dérivées partielles.